2017
DOI: 10.1042/cs20160001
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic and inflammatory basis of hypertension

Abstract: Hypertension is a major health problem with great consequences for public health. Despite its role as the primary cause of significant morbidity and mortality associated with cardiovascular disease, the pathogenesis of essential hypertension remains largely unknown. The central nervous system in general, and the hypothalamus in particular, are intricately involved in the development and maintenance of hypertension. Over the last several decades, the understanding of the brain’s role in the development of hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 176 publications
0
40
0
Order By: Relevance
“…Additionally, cytokines have different functions in the central nervous system and can induce neurotoxicity, which appears to contribute to the physiopathology of psychiatric [depression, schizophrenia] and neurodegenerative diseases [Parkinson’s and Alzheimer’s diseases] (Allan and Rothwell, 2003; Corsi-Zuelli et al, 2017; Dantzer et al, 2008). Moreover, since inflammation in the central nervous system, particularly in the hypothalamus, has recently been shown to be intricately involved in the development and maintenance of hypertension (Khor and Cai, 2017), we suggest that the selective and central anti-inflammatory potential of ADN stimulation could be an additional mechanism involved in the baroreflex anti-hypertensive effects.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, cytokines have different functions in the central nervous system and can induce neurotoxicity, which appears to contribute to the physiopathology of psychiatric [depression, schizophrenia] and neurodegenerative diseases [Parkinson’s and Alzheimer’s diseases] (Allan and Rothwell, 2003; Corsi-Zuelli et al, 2017; Dantzer et al, 2008). Moreover, since inflammation in the central nervous system, particularly in the hypothalamus, has recently been shown to be intricately involved in the development and maintenance of hypertension (Khor and Cai, 2017), we suggest that the selective and central anti-inflammatory potential of ADN stimulation could be an additional mechanism involved in the baroreflex anti-hypertensive effects.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have also confirmed that acupuncture can inhibit reflex hypertension through the opioid-mediated inhibition of glutamate in rVLM 32 . Therefore, glutamatergic suppression may further reverse the hypertensive effect of central TNF-α, which simultaneously recovers blood pressure and energy balance via inhibiting NF-κB and IKK β activation 33,34 (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise mechanisms by which CIH induces activation of neurons in the PVN and increases sympathetic nerve activity are incompletely understood. New evidence reveals that excessive oxidative stress and inflammation in the cardiovascular regulatory centers of the brain, particularly in the PVN, lead to neuronal activation and augmented sympathetic nerve activity in various forms of hypertension and other cardiovascular diseases ( Dange et al, 2015 ; Shen et al, 2015 ; Khor and Cai, 2017 ; Li Y. et al, 2017 ; Haspula and Clark, 2018 ; Jiang et al, 2018 ; Zhang et al, 2018 ). Microglia, the resident immune cells in the central nervous system, are often the major sources of pro-inflammatory cytokines in the central nervous system ( Kiernan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the PVN has been shown to increase sympathetic nerve activity and blood pressure in rats exposed to CIH ( Knight et al, 2011 ; Sharpe et al, 2013 ). Accumulating evidence indicates that oxidative stress and inflammation in the PVN are major contributors to the augmented sympathetic nerve activity in various forms of hypertension and other cardiovascular diseases ( Dange et al, 2015 ; Khor and Cai, 2017 ; Haspula and Clark, 2018 ; Jiang et al, 2018 ; Zhang et al, 2018 ). A recent study has demonstrated that CIH causes elevated oxidative stress and inflammation in the brain regions associated with neurodegeneration ( Snyder et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%